The interdisciplinary management of Severe burns in pregnancy - Christoph Wallner; Peter Kern; Norbert Teig; Marcus Lehnhardt; Björn Behr (Elsevier, 2017)
Background: Severe burns in pregnant women present an exceedingly challenging situation due to the limitation in therapeutic options including pain management and operative care.Case: We present a 30 years old patient, 38th week of pregnancy, who suffered a full thickness skin burns in 20% total body surface area and an inhalation trauma. In a Level-1 trauma center an interdisciplinary team of plastic surgeons, neonatologists and gynecologists was organized to deliver best patient care. Conclusion: This case presents a challenging situation with an intubated analgosedated pregnant woman, limiting treatment options. On admission a prompt cesarean delivery was performed to guard the unborn child. To shorten the hospital stay, a novel Bromelain based enzymatic debridement was performed on the full thickness burn wounds with immediate skin grafting. Keywords: Burn, Pregnancy, Management, Caesarean delivery